2013
DOI: 10.1345/aph.1r729
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VII Use in Critically III Patients: Clinical Outcomes and Thromboembolic Events

Abstract: While we cannot show direct causality between rFVIIa and the poor clinical outcomes documented in ICU patients, they provide important insight for critical care clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Table 5 shows the most common off-label uses of rFVIIa in our study. In this study, the most common off-label uses of rFVIIa were for cardiac surgery, ICH, and PPH, (33%, 18.8% and 11% respectively) which is comparable to that of other registries [18,19]. The majority of patients received a single dose (60%) and the mortality rate in this study is 58%, which is comparable to those seen in previous studies [12,[20][21][22].…”
Section: Discussionsupporting
confidence: 85%
“…Table 5 shows the most common off-label uses of rFVIIa in our study. In this study, the most common off-label uses of rFVIIa were for cardiac surgery, ICH, and PPH, (33%, 18.8% and 11% respectively) which is comparable to that of other registries [18,19]. The majority of patients received a single dose (60%) and the mortality rate in this study is 58%, which is comparable to those seen in previous studies [12,[20][21][22].…”
Section: Discussionsupporting
confidence: 85%
“…There was no difference in mortality between responders and nonresponders (68% and 69%, respectively, P = 0.9063). In 2013, a retrospective study reported on 1,459 critically ill patients in the ICU, of which 6% had cirrhosis, treated with rFVIIa . Patients treated with rFVIIa had higher mortality compared to controls (36% versus 16%, P < 0.0001), although they were found also to be sicker overall.…”
Section: Commentmentioning
confidence: 99%